2005
DOI: 10.1017/s0952523805224045
|View full text |Cite
|
Sign up to set email alerts
|

Toward a unified model of vertebrate rod phototransduction

Abstract: Recently, we introduced a phototransduction model that was able to account for the reproducibility of vertebrate rod single-photon responses (SPRs) (Hamer et al., 2003). The model was able to reproduce SPR statistics by means of stochastic activation and inactivation of rhodopsin (R*), transducin (G α ), and phosphodiesterase (PDE). The features needed to capture the SPR statistics were (1) multiple steps of R* inactivation by means of multiple phosphorylations (followed by arrestin capping) and (2) phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(145 citation statements)
references
References 102 publications
(273 reference statements)
9
135
1
Order By: Relevance
“…Previous models used Markov chains to account for the stochastic nature of the biochemistry (14,15) or partial differential equations to capture the complex OS geometry (16)(17)(18)(19), but here we unify these approaches into a single model. We further derive expressions for the dark noise power spectrum, which we use to estimate the values of key parameters from the analysis of dark current recordings in WT and GCAPs −/− knockout mice.…”
Section: Methods and Theorymentioning
confidence: 99%
“…Previous models used Markov chains to account for the stochastic nature of the biochemistry (14,15) or partial differential equations to capture the complex OS geometry (16)(17)(18)(19), but here we unify these approaches into a single model. We further derive expressions for the dark noise power spectrum, which we use to estimate the values of key parameters from the analysis of dark current recordings in WT and GCAPs −/− knockout mice.…”
Section: Methods and Theorymentioning
confidence: 99%
“…An additional issue depending on this answer in the visual system is the mechanism ensuring a remarkable reproducibility of single photon response in rods. One of the explanations of this reproducibility is based on the assumption that rhodopsin is deactivated through a large number of steps (52), the great majority of which is believed to be sequential phosphorylation by rhodopsin kinase (20,33,53,54), whereas in other models multiplicity of inactivation steps is not required (55). 4 Direct binding studies with numerous reconstituted fractions containing different phosphorhodopsin species suggest that as soon as light-activated rhodopsin has two to three phosphates, arrestin can bind it with high affinity (Fig.…”
Section: Journal Of Biological Chemistry 32079mentioning
confidence: 99%
“…The calculated light intensity at the retina was 2 scotopic Trolands, which would cause a considerable reduction in the rod dark current. 24 The device was driven by a rechargeable battery (Panasonic UL23300, Panasonic Corporation, Osaka, Japan) connected to a charge-pump chip (Max 1573, Maxim Integrated Products, Inc. Sunnyvale, CA, USA). The battery was recharged each morning.…”
Section: Lightmasksfconstruction and Designmentioning
confidence: 99%
“…There is Fast Track Paper Fast Track Paper considerable evidence to support this view. [13][14][15][16][17][18] These and other observations have led to a different proposal about the pathophysiology of DR. 19,[20][21][22] The oxygen demand of rods, in the outer retina, is much increased in darkness 6,7,13,[23][24][25] and this in turn causes a reduction in inner retinal oxygen tension. 11,25 It has been suggested that the increasing inner retinal hypoxia in diabetes causes the upregulation of cytokines, most importantly VEGF, to a degree that produces damage to small retinal vessels, thus reducing local capillary blood flow and increasing hypoxia in a vicious circle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation